2010
DOI: 10.1523/jneurosci.4255-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Morphine Induces AMPA Receptor Internalization in Primary Hippocampal Neurons via Calcineurin-Dependent Dephosphorylation of GluR1 Subunits

Abstract: Chronic morphine treatment resulting in the alteration of postsynaptic levels of AMPA receptors, thereby modulating synaptic strength, has been reported. However, the mechanism underlying such drug-induced synaptic modification has not been resolved. By monitoring the GluR1 trafficking in primary hippocampal neurons using the pHluorin-GluR1 imaging and biotinylation studies, we observed that prolonged morphine exposure significantly induced loss of synaptic and extrasynaptic GluR1 by internalization. The morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 66 publications
0
39
0
Order By: Relevance
“…These data strongly indicate that FKBP12 serves as an adaptor for the recruitment of PKC« and calcineurin. The fact that morphine can regulate the synaptic GluA1 subunit level of the a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor via its activation of calcineurin (Kam et al, 2010) suggests functions of these molecules in OPRM1 signaling beyond those that were explored in our study.…”
Section: Discussionmentioning
confidence: 82%
“…These data strongly indicate that FKBP12 serves as an adaptor for the recruitment of PKC« and calcineurin. The fact that morphine can regulate the synaptic GluA1 subunit level of the a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor via its activation of calcineurin (Kam et al, 2010) suggests functions of these molecules in OPRM1 signaling beyond those that were explored in our study.…”
Section: Discussionmentioning
confidence: 82%
“…The strength of synaptic responses can be altered by changes in either quantal content (releasing probability multiplied by number of releasing sites) or quantal size (postsynaptic response per synaptic vesicle), which is often estimated by measuring the amplitude and frequency of miniature excitatory postsynaptic potential or mEPSC responses (Del Castillo and Katz, 1954). Although both calcineurin and CaMKII have been reported to play roles in AMPA receptor trafficking during activity-dependent synaptic plasticity (Silva et al, 1992;Mulkey et al, 1994;Hayashi et al, 2000;Dell'Acqua et al, 2006;Kam et al, 2010), surprisingly, only calcineurin is necessary for morphine-induced reductions in the amplitude of AMPA receptor-mediated mEPSC responses (Fig. 7).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that chronic postsynaptic activation of MORs leads to two forms of plasticity of dendritic spines: loss of preexisting spines and loss of synaptic AMPA receptors (Liao et al, , 2007aKam et al, 2010). Here, we used our time-lapse live imaging system to clarify the signaling pathway that mediates morphine-induced spine loss (Fig.…”
Section: Inhibition Of Both Camkii and Calcineurin Preventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcineurin can also alter opioidspecific behaviors, because its inhibition decreases naloxoneinduced withdrawal symptoms in mice (Dougherty et al, 1987;Dougherty and Dafny, 1988;Homayoun et al, 2003) and can block conditioned place preference for morphine in mice (Suzuki et al, 1993;Motiei Langroudi et al, 2005). Calcineurin has also been linked to glutamate receptors after opioid exposure previously, because it can dephosphorylate AMPA receptors in chronic morphine-exposed primary hippocampal neurons that have undergone no withdrawal period (Kam et al, 2010). Because calcineurin appears to be able to alter NMDA receptors in models of withdrawal and reward, it too may be a component in long-term opioid-induced neural plasticity.…”
Section: Introductionmentioning
confidence: 99%